Effect of dexamethasone on brain oedema following acute ischemic stroke. - Shaikh, AK; Mohammad, QD; Ullah, MA; Ahsan, MM; Rahman, A; Shakoor, MA (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):450-458 The abstract of this article is available on the PubMed website